Moderne, postmoderne in metamoderne strukture občutenja - Kaluža, Jernej (Družboslovne razprave, 2025)
The article investigates the explanatory potential of metamodern memory that accommodates contradictions and reflects contemporary struggles over collective identity and its temporal dimensions. The authors examine the way memories of socialist Yugoslavia – particularly of Josip Broz – Tito – are articulated and mediated by generational, political and media dynamics. Based on big data analysis of 179 memory interviews conducted by undergraduate students with individuals born between 1940 and 1955, three structures of feeling are identified: a modern one centred on unity and progress, a postmodern turn marked by fragmentation and scepticism, and a metamodern sensibility that oscillates between sincerity and irony. Tito emerges as a symbolic figure whose meaning shifts across life stages and media representations. Relying on mixed methods, the authors trace how memories reflect evolving political contexts and media ecologies.
Keywords: Broz, Josip; communicative memory; Kolektivni spomin; komunikativni spomin; metamodern memory; metamoderni spomin; socialist Yugoslavia; socialistična Jugoslavija; structure of feeling; struktura občutenja; Tito